HMG-CoA Reductase Inhibition Promotes Neurological Recovery, Peri-Lesional Tissue Remodeling, and Contralesional Pyramidal Tract Plasticity after Focal Cerebral Ischemia - Kilic, Ertugrul; Reitmeir, Raluca; Kilic, Ülkan; Caglayan, Ahmet Burak; Beker, Mustafa Caglar; Kelestemur, Taha; Ethemoglu, Muhsine Sinem; Ozturk, Gurkan; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2014)
3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors are widely used for secondary stroke prevention. Besides their lipid-lowering activity, pleiotropic effects on neuronal survival, angiogenesis and neurogenesis have been described. In view of these observations, we were interested whether HMG-CoA reductase inhibition in the post-acute stroke phase promotes neurological recovery, perilesional and contralesional neuronal plasticity. We examined effects of the HMG-CoA reductase inhibitor rosuvastatin (0.2 or 2.0 mg/kg/day i.c.v.), administered starting 3 days after 30 min of middle cerebral artery occlusion for 30 days. Here we show that rosuvastatin treatment significantly increased the grip strength and motor coordination of animals, promoted exploration behavior and reduced anxiety. It was associated with structural remodeling of peri-lesional brain tissue, reflected by increased neuronal survival, enhanced capillary density, and reduced striatal and corpus callosum atrophy. Increased sprouting of contralesional pyramidal tract fibers crossing the midline in order to innervate the ipsilesional red nucleus was noticed in rosuvastatin compared with vehicle-treated mice, as shown by anterograde tract tracing experiments. Western blot analysis revealed that the abundance of HMG-CoA reductase was increased in the contralesional hemisphere at 14 and 28 days post-ischemia. Our data support the idea that HMG-CoA reductase inhibition promotes brain remodeling and plasticity far beyond the acute stroke phase, resulting in neurological recovery.